THE USE OF ANTIHYPERTENSIONS IN HYPERTENSION PATIENTS AT X HOSPITAL IN JEMBER - Ni Kadek Rani Kusuma Dewi (LPPM Universitas dr. Soebandi, 2024)
Background: Hypertension is the most common and common disease suffered by society. According to WHO (2023), hypertension is the third cause of death, because 1.28 billion people in the world suffer from hypertension. Hypertension sufferers at X Hospital Jember in 2022 are 4,774 patients. The increase in hypertension can be caused by risk factors, such as age, gender, obesity, lack of physical activity, smoking, stress, and consuming high levels of fat. The aim of the research is to determine the use of antihypertensive drugs in hypertensive patients at X Hospital Jember in 2023. Methods: This research is a non-experimental study with a retrospective descriptive research design. The data source in this research is the patient's electronic medical record data. Samples were taken using a total sampling technique which met the inclusion criteria as many as 44 patients. This research was conducted in the medical records room at X Hospital Jember with data for January-December 2022. Data is displayed in frequency and percentage form. Research results: During the research, it was found that almost half of the drug categories used a single drug with a percentage of 48%, and a small number of drug categories used a combination of three groups with a percentage of 11%. Based on drug class, almost half of them use ARB class drugs with a percentage of 27.3%. Based on drug type, almost half of the patients use candesartan drugs with a percentage of 27.3%. Based on the drug dose, a small percentage received a prescription for candesartan at a dose of 8 mg once a day with a percentage of 18.4%. Conclusion: Almost half of the use of antihypertensives in hypertensive patients at X Hospital in Jember is the ARB group, namely candesartan 8mg given once a day.